Ficções de uma autonomia possível - Santos, Júlia Carvalho dos (2016)
This work problematized the concept of autonomy and their relationship in the Psychiatric Reform. Initially the question was the production of autonomy linked to participation in political and social spaces of the Anti-Asylum Movement. But the concept of naturalization and the mistakes made produced by its various conceptions has drawn a distinction in the ways appears in the context of the Psychiatric Reform. In this sense, we as a device inserted in the diagram of madness, and then seek the definition of Spinoza the opening line to the modes of subjectivity. The field of research consisted in listening to two users of mental health services participants of social movements. Interviews open to a fictional dimension produced joints between the heard stories and fiction to give way to feelings and sensitivities of a potent way of life that dispenses the madhouse relations. From the perception of hardened movements in the interviews analysis time we let the discussion focused on the Anti-Asylum Movement spaces to discuss autonomy through emergency singularity. The ethical and methodological position of research-driven cartographic practice says research as knowledge production, and also the possibility of new forms of subjectivity by the intervention produced the reality that surrounds research.